CO2 mineralisation of Portland cement: Towards understanding the mechanisms of enforced carbonation. Issue 38 (May 2020) - Zajac, Maciej; Lechevallier, Aurore; Durdzinski, Pawel; Bullerjahn, Frank; Skibsted, Jørgen; Ben Haha, Mohsen
Highlights: Paper focuses on the carbonation mechanisms of the Portland cement clinker. For the first time, the correlation between the solution composition and the phase assemblage evolution was established. Carbonation reaction is fast, provided enough CO2 is present in the system. Carbonation reaction can be divided into three stages when the reaction is limited by the different levers. Main carbonation products are calcium carbonate and amorphous alumina silica gel containing calcium. Abstract: Reductions of CO2 emissions associated with Portland cement production represent currently the main challenge for the cement industry. A promising approach is to substitute the traditional hydration of cement by carbonation of cement clinker for the hardening of the material in concrete production. This work is a tailor-made experimental approach to explore the mechanisms of Portland clinker carbonation under wet conditions. The carbonation is found to be fast at the beginning of the reaction, provided enough CO2 is present in the system. Particularly, the calcium silicate phases react rapidly, where the kinetics is explained by the high undersaturation of these phases. Furthermore, the carbonation reaction can be divided into three stages when the reaction is limited by the different mechanisms: precipitation of products or dissolution of clinker or CO2 . The main carbonation products are calcium carbonate and amorphous alumina silica gel. These phases precipitate in a different locations forming a special microstructural pattern.